2023
DOI: 10.1039/d3ta02842a
|View full text |Cite
|
Sign up to set email alerts
|

Progressing thin-film membrane designs for post-combustion CO2 capture: performance or practicality?

Abstract: Tremendous potential is seen in membrane technology for realizing efficient post-combustion CO2 capture from power plant flue gas, the largest anthropogenic source of emission. However, an examination of existing literatures...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 214 publications
0
8
0
Order By: Relevance
“…This design space was formulated so that it does not significantly exceed the realistic range of permeances reported in the literature. The upper bound of CO 2 permeance (20,000 GPU) is based on the value suggested by Fujikawa et al While such performance has only been reported for nanomembranes, it is possible that some of the intrinsically high-performance membrane materials reported in the literature, when configured into hollow fibers with ultrathin (≈100 nm) selective layers, could yield such high permeance …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This design space was formulated so that it does not significantly exceed the realistic range of permeances reported in the literature. The upper bound of CO 2 permeance (20,000 GPU) is based on the value suggested by Fujikawa et al While such performance has only been reported for nanomembranes, it is possible that some of the intrinsically high-performance membrane materials reported in the literature, when configured into hollow fibers with ultrathin (≈100 nm) selective layers, could yield such high permeance …”
Section: Resultsmentioning
confidence: 99%
“…The upper bound of CO 2 permeance (20,000 GPU) is based on the value suggested by Fujikawa et al 6 While such performance has only been reported for nanomembranes, 31 it is possible that some of the intrinsically highperformance membrane materials reported in the literature, when configured into hollow fibers with ultrathin (≈100 nm) selective layers, could yield such high permeance. 32 The lower bound of 100 GPU has been reported for a blend membrane composed of carboxymethyl chitosan (CMC) and poly(amidoamine) (PAMAM) in the literature. 33 The lower bound of CO 2 /N 2 selectivity approximately was chosen to be close to the Knudsen selectivity value (≈1.8).…”
Section: Operability Studiesmentioning
confidence: 99%
“…The higher the separation factor, the higher the pore size requirement of the membrane, which needs to be precisely regulated. 102 The pore size of the gas membrane has to be between the size of the molecular diameters of the two separated gases, with a smaller pore size. In this case, there is a problem of relatively lower permeability.…”
Section: The Applications Of Cof Membranesmentioning
confidence: 99%
“…At the same time, the molecular adsorption is promoted through the coordinated regulation of the pore structure, which can further realise the efficient separation of gas or liquid mixture. 79 …”
Section: Applications Of Pof Membranesmentioning
confidence: 99%